AN IDENTITY ON SYMMETRIC POLYNOMIALS - Đặng Tuấn Hiệp; Lê Văn Vĩnh (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, we propose and prove an identity on symmetric polynomials. In order to obtain this identity, we use the interpolation theory, in particular, the Lagrange interpolation formula. In the proof of the identity, we propose two different proofs. The second proof will be the first step for our further studies related to identities on symmetric polynomials.